Association of Viral Infections With Oral Cavity Lesions: Role of SARS-CoV-2 Infection - La Rosa, Giusy Rita Maria; Libra, Massimo; De Pasquale, Rocco; Ferlito, Sebastiano; Pedullà, Eugenio (Frontiers in Medicine, 2021)
Different viral agents, such as herpesviruses, human papillomavirus, and Coxsackie virus, are responsible for primary oral lesions, while other viruses, such as human immunodeficiency virus, affect the oral cavity due to immune system weakness. Interestingly, it has been reported that coronavirus disease 2019 (COVID-19) patients can show cutaneous manifestations, including the oral cavity. However, the association between oral injuries and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is still unclear. This narrative review aimed to summarize the available literature and provide an overview of oral lesions associated with COVID-19. An online literature search was conducted to select relevant studies published up to November 2020. The results of 17 studies showed variability in oral lesions associated with COVID-19, including ulcerations, aphthous-like lesions, and macules. The tongue, lips, and palate were the most frequent anatomical locations. According to current knowledge, the etiopathogenesis of multiple COVID-19-associated lesions seems to be multifactor. The appearance of such lesions could be related to the direct or indirect action of SARS-CoV-2 over the oral mucosa cells, coinfections, immunity impairment, and adverse drug reactions. Nevertheless, COVID-19-associated oral lesions may be underreported, mainly due to lockdown periods and the lack of mandatory dispositive protection. Consequently, further research is necessary to determine the diagnostic and pathological significance of oral manifestations of COVID-19. All medical doctors, dentists and dermatologists are encouraged to perform an accurate and thorough oral examination of all suspected and confirmed COVID-19 cases to recognize the disease’s possible early manifestations.